2013
DOI: 10.1089/ten.tea.2012.0188
|View full text |Cite
|
Sign up to set email alerts
|

βig-h3 Potentiates the Profibrogenic Effect of TGFβ Signaling on Connective Tissue Progenitor Cells Through the Negative Regulation of Master Chondrogenic Genes

Abstract: Tendons and cartilage are specialized forms of connective tissues originated from common progenitor cells. Initial stages of differentiation of these tissues are characterized by the formation of cell aggregates, which share many molecular markers. Once differentiated, these cells retain considerable plasticity, and chondral metaplasia of tendon and fibrous connective tissues and eventual ossification often accompany degenerative diseases in the adult musculoskeletal system. While this fact is of great relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 49 publications
(80 reference statements)
3
22
0
Order By: Relevance
“…Sca1, a marker of pluripotent mesenchymal stem cells [35], was not regulated by TGF-β (Figure 1C). The results confirm previous studies indicating TGF-β promotes a fibrous phenotype in limb mesenchymal cells and extend the studies to sclerotome [13, 29, 31]. …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Sca1, a marker of pluripotent mesenchymal stem cells [35], was not regulated by TGF-β (Figure 1C). The results confirm previous studies indicating TGF-β promotes a fibrous phenotype in limb mesenchymal cells and extend the studies to sclerotome [13, 29, 31]. …”
Section: Resultssupporting
confidence: 92%
“…In addition, the cells in the culture were not round and took on a spindle shape [13]. Others have recently observed a similar response to TGF-β in limb mesenchyme grown in micromass culture [2931]. To further characterize the effects of TGF-β on sclerotome micromass cultures we treated cells with varying concentrations of TGF-β1 or BMP4 (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…They identified TGFβip as a factor downstream to TGFβ signaling (regulated by Smad 2 and 3), which is highly expressed in joint capsules and the differentiating tendons. Their findings indicated that TGFβip promotes the fibrogenic influence of TGFβ signaling in the pro‐fibrogenic pathway …”
Section: Discussionmentioning
confidence: 99%
“…We observed specific calcified structures in the M‐side of clubfoot for the first time (Figure ). This could bring a direct connection with overexpression of asporin (which plays a role in biomineralization), TGFβip (essential for TGFβ signaling), and the intracellular pool of TGFβ (relationships to collagen calcification) in the M‐side. Moreover Seki et al declared that overexpressed CILP suppressed TFGβ signaling in lumbal disc disease .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, it has been recently shown that it potentiates profibrogenic effects on connective tissue precursors under the control of TGFβ signalling (Lorda‐Diez et al. ).…”
Section: Discussionmentioning
confidence: 99%